PENGARUH PELATIHAN DAN KESEHATAN KESELAMATAN KERJA TERHADAP KINERJA KARYAWAN PT JASA ANGKASA SEMESTA - Novi Indah Susanthi; Iqlima Puspa Seruni (Institut Transportasi dan Logistik Trisakti, 2016)
PT. Jasa Angkasa Semesta (JAS) Halim Perdana Kusuma who tried field cargo handling and ground handling and has a network of cooperation with international and domestic companies. The problem in this research is the lack of employee training in understanding the Health Safety in the warehouse. The research objective was to determine the variable analysis training, Health Safety and Employee Performance, to solve the problems the author uses two (2) methods: the first method of field research sample population 30 and 30. Both methods of data analysis using multiple linear regression analysis, test validity, reliability test, t-test, f, the coefficient of determination. And the analysis and discussion show a proportional relationship between training, Health Safety and performance of employees that level of relationship variables classified in the strong category Health and Safety at Work provides a significant influence on employee performance variables.